Lower Cretaceous (Hauterivian-Albian) ammonite biostratigraphy in the Maestrat Basin (E Spain) - Garcia, R.; Moreno-Bedmar, J.A.; Bover-Arnal, T.; Company, M.; Salas, R.; Latil, J-L.; Martín-Martín, J.D.; Gomez-Rivas, E.; Bulot, L.G.; Delanoy, G.; Martínez, R.; Grauges, A. (Journal of Iberian Geology, 2014)
A review of the stratigraphic distribution of ammonoid species in the Lower Cretaceous (Hauterivian-Albian) of the Maestrat Basin (E Spain) was carried out. The specimens were mainly collected in the field by us and are stored in university or museum collections. Specimens from private collections and figured in the literature were also studied. We recognized 73 species that are distributed, in accordance with the latest version of the standard Mediterranean ammonite zonation for the Lower Cretaceous, in 14 ammonite zones: Acanthodiscus radiatus, Crioceratites loryi, Lyticoceras nodosoplicatum (Lower Hauterivian); Pseudothurmannia ohmi (Upper Hauterivian); Imerites giraudi (Upper Barremian); Deshayesites oglanlensis, Deshayesites forbesi, Deshayesites deshayesi, Dufrenoyia furcata (Lower Aptian); Epicheloniceras martini, Parahoplites melchioris, Acanthohoplites nolani (Upper Aptian); Leymeriella tardefurcata and Douvilleiceras mammillatum (Lower Albian). The recognition of these biozones allows a precise age calibration of the Maestrat Basin’s lithostatigraphic units that contain ammonoids as well as an associated indirect age calibration of the formations without ammonoids. Consequently, this report provides an updated, comprehensive and precise biostratigraphic framework, which aims to become a reference for the analysis of the Lower Cretaceous strata of the Maestrat Basin. The results are also relevant for the analysis of coeval ammonite-bearing sedimentary successions found in other Tethyan basins.